2019
DOI: 10.1101/850958
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Benchmark of tools for CNV detection from NGS panel data in a genetic diagnostics context

Abstract: Motivation:Although germline copy number variants (CNVs) are the genetic cause of multiple hereditary diseases, detecting them from targeted next-generation sequencing data (NGS) remains a challenge. Existing tools perform well for large CNVs but struggle with single and multi-exon alterations. The aim of this work is to evaluate CNV calling tools working on gene panel NGS data with CNVs up to single-exon resolution and their suitability as a screening step before orthogonal confirmation in genetic diagnostics… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In fact, benchmarking of several CNVs detection tools from exome data showed that a significant fraction of called CNVs are only present in a single tool [ 76 ]. It was demonstrated also that ExomeDepth is one the most balanced tools concerning sensitivity and specificity [ 77 ] and this latter was supported to be integrated with routine targeted NGS diagnostic services for Mendelian diseases [ 78 ]. Additionally, clinically relevant CNVs resulting from the different breast cancer studies highly depend on the bioinformatic tools and the methodology used to prioritize variants and to interpret results.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, benchmarking of several CNVs detection tools from exome data showed that a significant fraction of called CNVs are only present in a single tool [ 76 ]. It was demonstrated also that ExomeDepth is one the most balanced tools concerning sensitivity and specificity [ 77 ] and this latter was supported to be integrated with routine targeted NGS diagnostic services for Mendelian diseases [ 78 ]. Additionally, clinically relevant CNVs resulting from the different breast cancer studies highly depend on the bioinformatic tools and the methodology used to prioritize variants and to interpret results.…”
Section: Discussionmentioning
confidence: 99%
“…such as read depth analysis, paired-end mapping, or split read approach (43). Therefore, both SNVs and CNVs can be identified by NGS.…”
Section: Discussionmentioning
confidence: 99%
“…Nine out of sixteen disease-causing deletions only involved one to two exons (Table 1). With targeted NGS and CMA, the CNVs with small size are more likely to be missed (6,55,56). Our data showed that small CNVs affecting less than three exons can account for a significant portion of CNVs, and WGS can detect many of them with its unique combination of coverage depth and breakpoint detection.…”
Section: Only Pathogenic and Likely Pathogenic Deletions Were Identif...mentioning
confidence: 99%
“…However, because most CMA probes target the exons, when breakpoints are present in the introns or the intragenic regions, the identification of breakpoint location is much more difficult. Targeted-NGS-based CNV detection is becoming increasingly prevalent in recent years, however, they also pose similar weaknesses as CMA: the resolution is usually limited to two or more-consecutive exons, and the breakpoints cannot be mapped when they are located in non-targeted regions (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%